O Supremo Tribunal Federal durante a Assembleia Nacional Constituinte de 1987/88: o processo de delimitação de suas competências - Maieron, Alexandra Johann (2020)
The object of the present work is the Constituent Process, as well its political transformation in which is identified the involved actors and its stance. Seeks, moreover, critical reflections to the following questions: How was defined the competences of the Federal Court of Justice (Supremo Tribunal Federal - STF) in the constituent process of 1987/88 – that resulted of federal Constitution’s diction of the art. 102, now in force? Which actors participated? And, especially, which participation of the STF’s officers of the time – as well as its Judicial Power’s members in those deliberations? In this sense, these questions are discussed in the narrative. Namely, in the first and the second chapters, beyond the conceptual elements, the historical aspects of STF and the Competences attributed to it on the Constitutions of Brazil Republic are widely argued. As well as, in the third chapter, is evidenced descriptive highlighting in how the Federal Court of Justice and its representatives of the Civil Society, especially jurists, lawyers and magistrates, developed the debates in the court of the National Constituent Assembly of 1987/88. Therefore, wants to pursuit the understanding of the participants’ different opinions, they being the politicians of Federal Parliament, deputies, senators, jurists, doctrinators, professors, Judicial Power and Public Prosecution members, just as all the people involved in the definition of the Federal Court of Justice’s competences in the Federal Constitution of 1988. The research is organized in a documental analysis, using the deductive method to comprehend, in an analytical and descriptive way, the registered discussions in the Proceedings of the National Constituent Assembly. Thus, in the referred Constituent Process, is realized the predominance of the social movement of the participation, noted during the public audiences. However, regarding the STF’s competences prevailed the institutionalism and party political movements. Consequently, in the fourth chapter, the research reaches the redefinition of STF’s role in the social conformation of the Democratic state. Thereby, is understandable that the STF kept its juridical nature as constituent of PJ, but also assembled political competences as guardian of CF of 1988, what it transformed in one institution of hybrid powers, while the maximum entity of PJ, although, with political competences and powers when it comes of the constitutional control amplified by it. Briefly, the relevant legal competence of the STF is delimited, by means of a temporality and different views.